Application of titanium machining chips in welding consumables for wear-resistant hardfacing - Fagundes Junior, JosÃ© Gedael [UNESP] (2016)
Equipment of sugar cane plants and mineral extraction are submitted to severe abrasive wear conditions. Welded hardfacings are usually applied to repair this kind of damage, where commercial chromium/carbon-rich welding consumables have usually been employed. In the present work we investigated the microstructure of experimental hardfacings made by addition of residues (chips) collected from the machining of ASTM F67 (unalloyed Ti, grade 4) alloy. Mixtures with different carbide-formers (Cr/Nb ferro-alloys) were also tested. Two layers of ‘pure’ chips (Ti), chips plus Fe–Cr (Ti–Cr), and chips plus Fe–Nb (Ti–Nb) were applied on low-carbon steel specimens by the GTAW/TIG process. The microstructure of hardfacing layers was observed by optical and scanning electron microscopy (SEM) equipped with EDS microanalysis. The microstructural characterization has determined that carbide distributions change significantly with the chemical nature of the hardfacing. SEM observations coupled with EDS microanalysis have confirmed the formation of complex carbides within the metal weld, whose stoichiometry was determined by X-ray diffraction (XRD) analysis. Mixed carbides of MC type and some cementite have been found. As a result it was suggested that use of ASTM F67 chips as carbide formers for composition of welding consumables can contribute to improved wear resistance of hardfacings, if compared with traditional chromium-based hardfacings.